Settlement Quality Mapping Analysis Using Google Earth Imagery and GIS in Sorosutan Subdistrict, Yogyakarta City - Rakhmatika, M. (EDP Sciences, 2021)
Sorosutan Subdistrict is located in Umbulharjo Subdistrict, Yogyakarta City. The development of Sorosutan Subdistrict is so rapid as indicated by the density of settlements and the complexity of the problems in it. One of these problems is related to settlement conditions. The condition of Sorosutan Subdistrict which has a slum area needs to be investigated on the quality of its settlements through assessment, weighting, and interpretation of Google Earth Imagery. The stage of determining the quality of settlements in this research is interpreting the imagery and determine the scoring of each parameter of settlement quality using GIS software. Based on the analysis of the results of data processing, it was found that the quality of settlements in Sorosutan Subdistrict is partly of medium quality of 54.27, while good quality is 23.05 and bad quality is 22.68. The distribution of good and bad quality settlements dominates the western and southern parts of Sorosutan Subdistrict. The distribution of settlement quality dominates the eastern part of Sorosutan Subdistrict. Hamlets which are decided as slum settlements in these qualities of settlements assessment have bad qualities in hamlet numbers 004 and 015. Â© The Authors, published by EDP Sciences.